Does Intraoperative Blood Loss Affect the Short-Term Outcomes and Prognosis of Gastric Cancer Patients After Gastrectomy? A Meta-Analysis - Wen, Ze-Lin; Xiao, Da-Chun; Zhou, Xiong (Frontiers in Surgery, 2022)
Purpose The purpose of the current meta-analysis was to analyze whether intraoperative blood loss (IBL) influenced the complications and prognosis of gastric cancer patients after gastrectomy. Methods We systematically searched the PubMed, Embase and Cochrane library databases on November 29, 2021. The Newcastle-Ottawa scale was used to evaluate the quality of included studies. This meta-analysis uses RevMan 5.3 for data analysis. Results A total of nine retrospective studies were included in this meta-analysis, involving 4653 patients. In terms of short-term outcomes, the Larger IBL group has a higher complication rate (OR=1.94, 95% CI=1.44 to 2.61, P<0.0001) and a longer operation time (OR=77.60, 95% CI=41.95 to 113.25, P<0.0001) compared with the smaller IBL group, but the Larger IBL group had a higher total retrieved lymph nodes (OR=3.68, 95% CI=1.13 to 6.24, P=0.005). After pooling up all the HRs, the Larger IBL group has worse overall survival (OS) (HR=1.80, 95% CI=1.27 to 2.56, P=0.001) and disease-free survival (DFS) (HR=1.48, 95% CI=1.28 to 1.72, P<0.00001). Conclusion Larger IBL increased operation time and postoperative complications, and decreased OS and DFS of gastric cancer patients. Therefore, surgeons should be cautious about IBL during operation.